2012
DOI: 10.5812/jjm.4071
|View full text |Cite
|
Sign up to set email alerts
|

A Study of The Genetic Variability of Blastocystis hominis Isolates in Hamadan, West of Iran

Abstract: Blastocystis hominis is a common protozoan parasite in the human and many other animals intestine. The parasite pathogenicity is still controversial. A few studies have been conducted on prevalence of B. hominis subtypes in Iran. The results of present study improve our knowledge on B. hominis subtypes in Iran and therefore we can do more investigations on pathogenicity potential of these subtypes in the future. Background:Blastocystis is a common protozoan parasite in mammals, birds, amphibians, reptiles, fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(36 reference statements)
2
10
1
Order By: Relevance
“…isolated from humans, 19,21,[23][24][25] whereas two studies reported a higher incidence of subtype 1 in humans. 20,26 In contrast to our study, Khoshnood et al reported the ST4 was the most prevalent subtype in human samples. 22 Generally, subtypes 3 has been identified as the most common subtype in human.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…isolated from humans, 19,21,[23][24][25] whereas two studies reported a higher incidence of subtype 1 in humans. 20,26 In contrast to our study, Khoshnood et al reported the ST4 was the most prevalent subtype in human samples. 22 Generally, subtypes 3 has been identified as the most common subtype in human.…”
Section: Discussioncontrasting
confidence: 99%
“…Molecular studies on Blastocystis previously conducted in Iran showed ST1, ST2, ST3, ST4, ST5, ST6 and ST7 in humans, and ST3 was reported in all studies performed in Iran. [19][20][21][22][23][24][25][26][27] The subtype 3 was the most prevalent subtype of Blastocystis in our study, which is similar to the several studies performed in Iran about the subtype distribution of Blastocystis sp. isolated from humans, 19,21,[23][24][25] whereas two studies reported a higher incidence of subtype 1 in humans.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Three subtypes, including ST1 (56.1%), ST3 (22%) and ST2 (7.3%) were characterized. Coexistence of ST1 and ST3 was detected in 14.6% of cases ( 22 ). In another study in Iran, 100 Blastocystis isolates were characterized using seven pairs of STS primers.…”
Section: Discussionmentioning
confidence: 99%
“…subtype 1 (ST1) following ST3 was not surprising. There were various reports which showed ST1 was the common subtype found in human, together with ST2, ST3 and ST4 [ 39 , 41 , 42 ]. The single infection of Blastocystis subtype 6 (ST6) may reflect zoonotic transmission, as this subtype has been reported among the avians [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%